2021
DOI: 10.3390/polym13020257
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Poly(ε-Caprolactone)/Hydroxyapatite Scaffolds Modified with Alkaline Hydrolysis Enhance Osteogenesis In Vitro

Abstract: The 3D-printed bioactive ceramic incorporated Poly(ε-caprolactone) (PCL) scaffolds show great promise as synthetic bone graft substitutes. However, 3D-printed scaffolds still lack adequate surface properties for cells to be attached to them. In this study, we modified the surface characteristics of 3D-printed poly(ε-caprolactone)/hydroxyapatite scaffolds using O2 plasma and sodium hydroxide. The surface property of the alkaline hydrolyzed and O2 plasma-treated PCL/HA scaffolds were evaluated using field-emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…A previous work compared the differentiation potential of PCL and PCL/HA scaffolds with hDPCs, human umbilical cord mesenchymal stem cells (MSCs) and human bone marrow derived MSCs, with the hDPSCs presenting superior osteogenic outcomes [41]. Other have been successfully applying hDPSCs for the evaluation of PCL/HA scaffolds for bone tissue regeneration [46,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…A previous work compared the differentiation potential of PCL and PCL/HA scaffolds with hDPCs, human umbilical cord mesenchymal stem cells (MSCs) and human bone marrow derived MSCs, with the hDPSCs presenting superior osteogenic outcomes [41]. Other have been successfully applying hDPSCs for the evaluation of PCL/HA scaffolds for bone tissue regeneration [46,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Specific biomaterials such as those mentioned above and living cells become the ink needed to print scaffolds and structures on which cells are seeded. This technology is also applied to dentistry and a recent study demonstrated that DPSCs grown on a scaffold obtained with different biomaterials and printed with the 3D bioprinter show high cell viability and osteogenic differentiation as well as mineralization comparable to more canonical cell culture [ 107 – 109 ].…”
Section: Overview Of Different Types Of Dental Stem Cellsmentioning
confidence: 99%
“…All subjects were undergoing extractions as a part of routine orthodontic or periodontal therapy. The sample size determination was conducted based on previous studies that have performed similar studies on stem cells [13,14]. However, sample size is not a critical determinant in stem cell experiments as stem cells have uniform properties and are cultured through many passages for the tests.…”
Section: Sample Size Determination and Sample Collectionmentioning
confidence: 99%